The assassination of Lumumba - Witte, Ludo de. (London Verso, 2001)
Patrice Lumumba, first prime minister of the Republic of Congo and a pioneer of African unity, was murdered on 17 January 1961.
Includes bibliographical references (p. [204]-210)
Keywords: Lumumba, Patrice, 1925-1961 -Assassination.